2018
DOI: 10.1515/tnsci-2018-0023
|View full text |Cite
|
Sign up to set email alerts
|

Tuberous sclerosis complex: Clinical spectrum and epilepsy: A retrospective chart review study

Abstract: Tuberous sclerosis complex (TSC) is an autosomal dominant genetic neurocutaneous disorder, with heterogeneous manifestations. We aimed to review the clinical presentation of TSC and its association with epilepsy among Saudi population. This was a retrospective chart review study of 88 patients diagnosed with TSC with or without epilepsy. In 38.6% of patients, symptoms began before 1 year of age. The most frequent initial manifestations of TSC were new onset of seizures (68.2%), skin manifestations (46.6%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
11
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 29 publications
5
11
2
1
Order By: Relevance
“…Our patient with AML was 9 years old. Although the incidence rate in the literature was different, the frequency of AML in our study was lower [10,11] . Chromosomal studies in TSC identified two genes.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Our patient with AML was 9 years old. Although the incidence rate in the literature was different, the frequency of AML in our study was lower [10,11] . Chromosomal studies in TSC identified two genes.…”
Section: Discussioncontrasting
confidence: 73%
“…In our study, 9 (56.2%) out of 16 patients presented with convulsions. The prevalence of seizure as one of the initial TSC manifestations was lower than those recently reported from the studies published by Almoberak et al, [10] Wilbur et al, [4] Sing Au et al, [7] and İncecik et al [8] at 68.2%, 91%, 74.8%, and 89.1%, respectively. Similar results were found in the studies by Saltuk et al [11] at 42.8% and Rubilar et al [12] at 48.7%.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…As noted previously, TSC is highly variable in its clinical presentation and symptoms can develop and change throughout life. Since milder cases may potentially go undetected, the incidence of TSC may be underestimated [25].…”
Section: Discussionmentioning
confidence: 99%
“…Although infantile spasms are common, all types of seizures may occur with advancing age(11). The frequency of epilepsy in patients with TSC has been reported as being 53-85% in different studies(10,(12)(13)(14). riod and increase with age, causing hypertension, hematuria or renal failure(16,17).Kingswood et al (17) investigated 2216 patients registered to the TuberOus SClerosis registry to increase disease Awareness (TOSCA) and found renal angiomyolipoma (AML) in 51.8% of 2065 patients who had renal imaging.…”
mentioning
confidence: 99%